PENERAPAN METODE FIRST IN FIRST OUT (FIFO) DALAM SISTEM ANTRIAN PELAYANAN ADMINISTRASI MAHASISWA: Studi Kasus: DAAK Universitas AMIKOM Yogyakarta - Moch. Farid Fauzi; Alfie Nur Rahmi (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Queuing can be interpreted as a process starting from the arrival of customers, waiting to be served, to getting service. Queuing system that is not well organized can hamper service. Therefore, along with the development of information technology, many queuing systems have been developed. This study aims to build a system with case studies at AMIKOM University Yogyakarta. Administrative services that exist on the object sometimes cause long queue problems, especially when trouble occurs when filling out the KRS which results in some students having to come directly to campus. Based on the description of the problem, researchers are interested in designing a website-based queuing system by applying the First In First Out (FIFO) method. FIFO is a method of solving the queuing problem that can be applied in a way that the first entry is assumed to be the first out.